Incidence of post-harvest fungal rots of kinnow mandarin and their management - VERMA*, V.S. (Indian Phytopathology, 2009)
Various fruit rots caused by seven fungal pathogens isolated from diseased kinnow mandarin fruits during the entire marketing period from November to April next were green mold rot (Penicillium digitatum, P. italicum, P. chrysogenum), black mold rot (Aspergillus niger), core rot (Alternaria alternata), soft rot (Fusarium moniliforme) and stem-end rot (Botryodiplodia theobromae). The periods of fruit rot by fungal pathogens varied depending upon the prevailing temperature and humidity during their post-harvest journey in the marketing chain. The seasonal disease incidence of kinnow fruit clearly marked two distinct peaks of fungal rot spoilage. Out of a cumulative monthly fruit loss of 7.77-14.20% due to rot from November to April, the major fruit spoilage during this period was dominated by green and blue mold rots caused by P. digitatum (5.18-8.85%) and P. italicum (2.59-4.82%) with peak rot losses in January (8.25%)-February (8.85%) and February (4.82%)-March (4.43%), respectively. The second peak was dominated by green and black mold rots caused by P. chrysogenum and A. niger with a fruit spoilage of 3.67% by each pathogen during warmer month of April. The average monthly loss due to fruit rot during the entire marketing season was 11.61%. Postinoculation chemical treatments were ineffective against the major fruit rot pathogens. Pre-inoculation treatments of thiabendazole (0.05%), benlate (0.05%) and carbendazim (0.05%) were highly effective against green and blue mold rots caused by P. digitatum and P. italicum, respectively followed by salicylic acid (0.05%), sodium metabisulphite (0.5%) and borax (6%) whereas thiophanate methyl (0.25%) and borax (6%) were most effective against black mold rot caused by A. niger.